A Stringent but Critical Actualist Subjectivism about Well-Being - Lemaire, Stéphane (Les ateliers de l'éthique / The Ethics Forum, 2016)
Subjectivists about well-being claim that an object is good for someone if and only if this individual holds a certain type of pro-attitude toward this object. In this paper, I focus on the dispute among subjectivists that opposes those who think that the relevant pro-attitudes are actual to those who think that they are counterfactual under some idealized conditions. My main claim is that subjectivism should be stringently actualist, though our actual pro-attitudes may be criticized from an intrinsic perspective. To defend this claim, I first present three desiderata that a subjectivist theory of well-being should fulfil. Two of these desiderata result from the fact that a subjectivist theory of well-being should not be implicitly paternalist, while the other is that it should be able to play a normative role. I then show that several actualist theories that introduce light forms of idealization or other conditions that have a similar aim, fail to satisfy at least one of the antipaternalist desiderata. This gives some legitimacy to a very stringent version of actualism. I then describe three features of the kind of stringent actualism that I want to defend, which will explain the ability of what is good for someone to play its normative role. Finally, I show how these features allow us to deal with the classic objection that the objects of actual “defective attitudes” cannot be good for the holder of these pro-attitudes.